COUNTER-HEGEMONY PRACTICE A LA GOJEK DRIVER-PARTNERS INFLUENCERS (International Conference on Social and Islamic Studies, 2021)
The sharing economy business model implemented by Gojek posits its motorbike drivers as partners with the status of independent contractors. However, some empirical studies show the practices of asymmetrical working relationships and place Gojek's driverpartners as the exploited party. Gojek's business is hegemonic since the exploitation practices wrapped in affective ways, e.g. through the concept of partnership that glorifies freedom and flexibility and the gamification strategy used in the application. In the context of this new emerged business practice, there is a vagueness about the legal status of the driver-partners. This is merely a corporate strategy to avoid the obligation to provide social protections for drivers due to their non-employee status. However, in the midst of hyperexploitation practicescarried out by the corporation, several studies have revealed actions of resistance conducted by driver-partners, ranging from demonstrations, boycotts, to various uses of application modification. In contrast to previous studies, using multimodal discourse analysis method, this paper particularly elaborates a form of counter-hegemony action carried out by three Gojek driver-partners who become influencers (media social users that have plenteous followers). Their affliction as Gojek driver-partners who often experience income deficiency due to the high competitiveness and the complicated platform work system, are used to accumulate social and economic capital.